Digital transformation of society and culture: features of the formation of media reality - Kolyadko, Ilya N. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article analyses the most important aspects of digital transformation of society and culture in the conditions of creating a unified communication space. It is established that the system of worldview universals undergoes significant changes under the influence of modern information and communication technologies. The idea that the emerging world pictures and images of reality determine a different vision of the same facts is emphasised. It is revealed that the event-based nature of media reality allows constructing desired perceptions of the world by reproducing stereotypes of thinking, behaviour and activity supported by mass media. The challenge arising in the process of digital transformation of society and culture, which implies the use of modern information and communication technologies and media technologies to manipulate collective and individual consciousness, is considered. The analytical potential of philosophical reflexion as a means of rational explication of the world picture adequate to reality in the periods of transformation of the foundations of society and culture is revealed. The analytical potential of philosophy and its role in the constitution of social order and stability are defined.